Growth and Productivity of Tidore Local Chili (Capsicum sp) with Green Fertilizer on Marginal Soil Type in Campus IV Area of Khairun University - Abdullah, Hayun; Mahmud, Shubzan Andi; Haryanto, Sugeng; Abdullatif, Zauzah (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study explores the potential of weeds as a source of green fertilizer to increase the growth and production of local Tidore chilli plants (Capsicum annuum L) on marginal land. Using a Random Group Design, five green manure treatments were tested, namely without green manure (control), Clotalaria juncea, Ageratum conyzoides, Cassia tora, and Colopogonium mucanoides. The analysis showed that using Crotalaria juncea green fertilizer significantly impacted plant height, number of primary branches, petioles, and flowers and fruits. This green fertilizer also increases the fruit's fresh weight, with the highest average reaching 296.50 g in the 4th harvest. These findings show that using weeds as green fertilizer can be a sustainable alternative to improve soil fertility and agricultural productivity on marginal land.